Pengaruh Motivasi dan Lingkungan Kerja terhadap Kinerja Karyawan - Siti Latifah; Sudarijati Sudarijati; Samsuri Samsuri (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
The purpose of the research is to determilne the conditions of motivation, work environment and employee performance, the influence of motivation and work environment simultaneously on employee performance, the influence of motivation and work environment partialy on employee performance. The research design used al qualitative-quantitative approach or a mixed method wilth descriptive and specific methods, and used secondary data. The subject of this research is PT Arkha Jayanti Persada Citeureup-Bogor and the object of this research ils permanent employees at PT Arkha Jayanti Persada Citeureup-Bogor. The analysis tool uses multilple linear regression, F test and t test with a probability level of five percent. The results showed that the responses of employees regarding motivation were in the high category, the responses of employees regarding the work environment were in good categories and the responses of employees regarding the performance of employees were in good categoriles. Conclusion, Silmutaneousy motivation and work environment have a positive and significant effect on employee performance. Partially motivation has a positive and significant effect on employee performance, and the work environment has a positive and significant effect on employee performance. Keyword : Employee Performance Work Motivation, Work Environment